CONCATENATING POSTGRADUATE THESIS DESIGN WITH SOCIAL SCIENCE RESEARCH - Santi Widiastuti; Sugiarto (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
Main Objective: The main objective of this study is to empower designers to collaborate with researchers in other disciplines — especially in the social sciences — by articulating a design inquiry model that can be implemented in a master's program in design. Background problems: Modern research problems are complex and design needs to be better integrated with the social sciences and play an equal role in addressing them. A final master's degree in design prepares students for this integration, but design activity should be evidence-based rather than viewed retrospectively as a form of research without change. We need to adapt to ultimately contribute to research. Novelty: There are main criteria for design-based inventions in this study, including value, relevance, novelty, focus, transferability, and practicality. When these criteria are met, investigations can operate within the social sciences, or they can be leveraged and serve as the discovery phase in evidence-based inquiry. Research Method: This study presents design-based discovery, a design inquiry model that places design in the theory development cycle as theory building, not theory testing. This research, therefore, uses a design inquiry model approach, (invention-based design) in other disciplines by articulating a design inquiry model that can be implemented in a master's program in design to be complementary and compatible with social science research. Finding/Result: A proposed design inquiry model with design exploration serving as the research discovery phase guiding the design activity to make specific contributions to areas of social science that are outside of design. It involves a careful process with six investigative components, all ultimately connecting the knowledge base beyond design to design exploration. Conclusion: This study proposes six main criteria for design-based inventions: value, relevance, novelty, focus, transferability, and practicality. In the model proposed in this study, the six investigative components are described and supported with examples. Notably, the investigative component includes a standardized format for research questions, as well as the derivation of design principles from processes that involve exploration rather than one that generates solutions. This model can easily be adopted in other master programs with the necessary resources. In addition, this model, if placed in design activities in evidence-based research practices, can become wider. There is no claim that a designer's self-reflection equates to a strictly social science method so design researchers must continue to study design and build on their knowledge of the discipline. Keywords: Design Thesis, Social Science, Postgraduate Thesis Design